Pemberdayaan Masyarakat Dalam Pengelolaan Sampah Rumah Tangga Melalui Metode 3R (Reduce, Reuse, Recycle) - Rais, Rinovian; Jamin, Nunung Suryana; Sallo, Andi Kamal M.; Aripa, Lusyana (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Household waste management is a major challenge for the community, especially in densely populated areas. The 3R (Reduce, Reuse, Recycle)-based community empowerment program is one solution that can increase awareness and active participation of the community in managing waste independently and sustainably. This community service activity aims to increase community knowledge and skills in sorting and processing household waste through the 3R method. The method of implementing the activity includes counseling, recycling practice training, and assistance in waste management. The results of the activity show an increase in community understanding of the importance of waste management and the formation of environmental activist groups that are active in 3R activities. This program has a positive impact on reducing the volume of household waste and improving environmental quality.